Analysis of Added Value of Coconut Processing into Virgin Coconut Oil (VCO) in The Al-Huda Household Business in Lasalepa Village Lasalepa District Muna Regency - Rahma Dita; Ilma Sarimustaqiyma Rianse; Munirwan Zani (International journal of technology and education research, 2023)
This study aims to determine the process of processing coconuts into Virgin Coconut Oil (VCO) and the amount of added value obtained from processing coconuts into Virgin Coconut Oil (VCO) in the Al-Huda household business in Lasalepa Village, Lasalepa District, Muna Regency. This research was conducted in December 2022-April 2023 and used primary and secondary data types and sources. Analysis of the data used to determine the process of processing coconut into VCO is a qualitative descriptive analysis and to determine the value added from processing coconut into VCO using Hayami's added value analysis method. The results showed that the process of processing coconut into VCO went through several stages, namely: peeling and cleaning the coconut flesh, grating and squeezing the coconut milk, separating water and coconut juice, fermentation, filtering and packaging. Meanwhile, the additional value obtained from processing coconut into VCO is IDR 36,008/kg coconut, where this value consists of business or processing profits of IDR 32,883 and labor benefits of IDR 3,125. Remuneration for the owners of production factors is the largest in operating profit of 87.7% while labor income is 8.3% and the contribution of other inputs is 4%.